PENGADAAN DESTINASI WISATA EDUKASI DAN RUANG TERBUKA SEBAGAI UPAYA OPTIMALISASI WISATA KOTA TUA - Michelle Quinsa Tanudjaja; J.M. Joko Priyono Santoso (Jurusan Arsitektur dan Perencanaan, 2022)
Jakarta Old Town, jakarta, Indonesia, is one of the domestic and foreign tourism destinations, that should be full of dynamic and potential to be developed into one of Jakarta’s heritage education tourisms. In reality, according to the questionnaire, tourists are more drawn to visiting other tourist destinations like Ancol (Jakartabay). This is caused by the views of the public who judge museums to be old haunted builings and boring because the lack of interesting programs and unfriendly facilities provided for pedestrians. To increase tourist’s interest, using the urban acupunture method, as a step to fixing Jakarta Old Town. That is to add more modern attraction programs such as rest areas and culinary spots, not forgetting the contextual history of the area while also being instagenic, a trend which people likes to upload their daily life on social media. Using literature studies, field survey and questionnaire, collected accurate data. The analysis and synthetic process is done to find programs along with the best location to be made into an acupunture point. The location of the site is included in the Old City area, that was once included in Batavia wall, famous for it’s colonial style buildings. Guidelines from provincial government regarding the develoment of Jakarta Old Town, making this area a cultural heritage tourism destination and educational tourism. Project presenting a function compatible to these provisions. The outcome of this project is a Batavia acculturation cultural education tourism destination, a rest area, and performance area with promenade beside Ciliwung River. This project is meant to become a generator in the area, while also become a tourist attractor from outside the area. With an architectural style that juxtaposes Dutch colonial architecture and modern. Modern Architecture aims to remind the imperialism characteristics into architecture. Accompanied by the proposed changes to the trafic system and the main modes of transportation in the area. Keywords: urban acupunture; Jakarta Old Town; Education Tourism; Jakarta Tourism; Cultural Tourism Abstrak Kota Tua Jakarta, Indonesia merupakan salah satu destinasi wisata domestik dan mancanegara, yang seharusnya penuh dengan dinamika dan potensi untuk dikembangkan menjadi salah satu heritage education tourism Jakarta. Kenyataannya bedasarkan kuisioner, wisatawan lebih tertarik untuk mengunjungi destinasi wisata lainnya seperti Ancol (Jakartabay). Hal ini disebabkan oleh pandangan masyarakat yang menilai museum sebagai bangunan tua angker dan membosankan karena kurangnya program yang menarik dan kurang bersahabatnya fasilitas pedestrian. Demi meningkatkan minat wisatawan, digunakan metode akupunktur perkotaan, sebagai langkah perbaikan Kota Tua Jakarta. Yaitu menyuntikan program atraksi yang lebih moderen seperti area peristirahatan dan kuliner, tanpa melupakan sejarah kontekstual kawasan dan sekaligus instagenic yang merupakan tren masyarakat yang suka mengunggah kesehariannya ke media sosial. Menggunakan studi literatur, survey, kuisioner dikumpulkan data yang akurat. Proses analisis sintesis dilakukan untuk menemukan program serta lokasi yang tepat untuk titik akupunktur. Lokasi tapak termasuk dalam kawasan Kota Tua yang dulu termasuk dalam tembok Batavia, terkenal dengan gaya bangunan kolonialnya. Guidelines dari pemprov terkait pengembangan Kawasan Kota Tua Jakarta, menjadikan kawasan ini sebuah destinasi wisata cagar budaya dan wisata edukasi. Proyek menghadirkan fungsi yang sejalan dengan ketentuan tersebut. Hasil akhir dari proyek ini adalah destinasi wisata budaya Batavia, tempat peristirahatan, serta area pertunjukan dengan promade disisi Sungai Ciliwung. Proyek ini dimaksudkan menjadi generator dalam kawasan, sekaligus menjadi atraktor wisatawan dari luar kawasan. Gaya arsitektur yang menyandingkan arsitektur Kolonial Belanda dan moderen. Arsitektur moderen bertujuan untuk mengingatkan kembali karakteristik imperialisme ke dalam arsitektur. Disertai dengan usulan perubahan sistem lalu lintas dan moda transportasi utama dalam kawasan.